Strategi Komunikasi Lembaga Penjaminan Mutu Pendidikan Sumatera Utara dalam Implementasi Sistem Penjaminan Mutu Internal - Jonnedi Jonnedi; Rahmanita Ginting; Yan Hendra (JURNAL SIMBOLIKA: Research and Learning in Communication Study (E-Journal), 2020)
This study aims to determine the communication strategy and communicationstrategy barriers used by the North Sumatra Education Quality Assurance Institute as one of the government agencies domiciled in each province and responsible for implementing quality assurance as an extension of the central government in the implementation of the Internal Quality Assurance System to meet and improve the quality of education. This research was carried out at SMP Negeri 4 Tanjung Morawa and SMP Negeri 2 Pancur Batu, Deli Serdang Regency, North Sumatra Province. The data is collected through interviews, observations and analyzed using descriptive analysis methods with a qualitative approach. This study uses Harold Lasswell’s Communication Theory. The result showed that the communication strategy of the North Sumatra Education Quality Assurance Institute takes the form of coordination meetings, technical guidance, assistance, monitoring and evaluation. Obstacles that arise in carrying out the communication strategy are the ability to operate technology, the location of the implementation of technical guidance and power outages (technical barriers); the large number of unfamiliar terms in the delivery of material makes it difficult for participants to understand the material (semantic barriers); and the lack of willingness of the school or the Education Quality Assurance Team to change (behavioral barriers).